(untitled) (Research, Society and Development, 2021)
Introduction: The aging process is a risk factor for neurological diseases such as Alzheimer’s disease. Omega 3 is a fatty acid present in neuronal membranes and plays a fundamental role in the metabolism of nervous tissue. Objective: to describe the effects of using omega 3 in the treatment of patients with Alzheimer’s Disease. Method: this is an integrative review developed in LILACS, MEDLINE AND EMBASE databases using the descriptors: Alzheimer Disease, Omega-3 Fatty Acids, Therapeutics and Disease Prevention. 483 articles were found, but 476 did not meet the eligibility criteria and were excluded. A comparative analysis of the data extracted from the articles selected for the final sample was carried out. Results: The sample consisted of seven articles. There was a prevalence of the use of capsules containing 800 mg of docosahexaenoic acid and 225 mg of eicosapentaenoic acid. Fatty acids have been shown to have the potential to reduce the accumulation of beta amyloid proteins in cortical regions of the brain or even prevent formation, in addition to increasing cortical thickness. Conclusion: Supplementation with omega 3 has beneficial effects in the treatment of patients with Alzheimer’s, as it has neuroprotective characteristics in combating morphophysiological changes that normally occur in the pathological environment.